Common patterns in the public reporting of waiting time and waiting list information: Findings from a sample of OECD jurisdictions. Issue 8 (August 2021) - Lee, Mandy; Martin-Carroll, Margaret; von Mollendorff, Wendy; Condon, Claire; Kavanagh, Matthew; Thomas, Stephen
Highlights: Start and end-points of waiting time measures for elective treatment are compared Three patterns of waiting time targets identified covering different patient pathway sections Time-to-treatment measures vary hugely: from point of referral or from patient waitlisted Reported statistics are commonly based on "completed waits" rather than "ongoing waits" Commonly reported statistics: Median waiting time, treatment volume, and time-to-treatment as KPI Abstract: We present findings from a review of published literature and administrative documentation on waiting time and waiting list reporting models for elective treatment in a sample of international jurisdictions (a subset of OECD countries, with regional reporting regimes treated as distinct jurisdictions). In this paper we identified common patterns in the measurement and reporting of waiting time and waiting list information for elective treatment. We mapped the waiting time, waiting list, and key performance indicator statistics reported by 15 English-speaking international jurisdictions. Three distinct patterns of maximum waiting time target measures for elective treatment were identified amongst our international sample following our patient pathway event time-point analysis: (i) full-pathway maximum wait time targets; (ii) separate wait time targets for "time-to-diagnosis" and "time-to-treatment"; and (iii) "Time-to-Treatment" waiting time target only. Our review also revealed common patterns in the reporting of waiting time and waiting list statistics as well as KPI measures amongst a sub-sample of English-speaking jurisdictions. These common patterns provide a starting point towards more standardised measurement and reporting of waiting time and waiting list statistics in benchmarking access to elective care internationally.